PENGARUH METODE RESITASI OLEH GURU PENDIDIKAN AGAMA KRISTEN TERHADAP KEAKTIFAN BELAJAR SISWA - Asima Rohana Rohana Lumban Tobing (IAKN Tarutung, 2019)
Abstract,- The purpose of this study is to determine the positive and significant effect between recitation methods of Christian Religion Education teachers on students learning active of class VIII SMP N 1 Balige in academic year 2018/2019. This study is a correlation study that uses descriptive and inferential statistical techniques. The results of the analysis show that Fcount=12,44Ftable=2,00, then H0 is rejected and Ha is accepted. It means that there is a positive and significant effect between the recitation method of Christian education teachers on students learning active of grade eight in SMP Negeri 1 in Balige in academic year 2018/2019 was 24,60%. Keywords: Recitation Method, Student Learning Active